Game Adventure 3D Pengenalan Bangunan Bersejarah Minahasa Selatan: 3D Adventure Game Introduction to South Minahasa Historical Buildings - Christian Leonard Cliff Liem; Sherwin R. U. A. Sompie; Brave A. Sugiarso (Universitas Sam Ratulangi, 2023)
Abstract — History is an event that actually happened and concerns about human life and will provide us with information about the glory of the culture in the past. Historical events that have occurred will end and leave a heritage. Indonesia has various types of heritage, such as the heritage of various historical buildings. Especially in South Minahasa, it has traces of heritage in the form of buildings. There are the Veldbox Tumpaan and Portuguese Fort Amurang. The rapid development of technology makes various types of technology emerged that can be used as educational tools, for example games. This study aims to create a game that can introduce historical buildings in South Minahasa using the MDLC (Multimedia Development Life Cycle) method. This game is made in 3 dimensions and an adventure genre. Based on the results of the research and the questionnaires carried out, it was concluded that there was an increase in user knowledge, also this game could be an alternative media in introducing historical buildings in South Minahasa. Key words— Game; Minahasa; Buildings; History Abstrak — Sejarah merupakan peristiwa yang benar-benar terjadi dan menyangkut tentang kehidupan manusia serta akan memberikan kita informasi mengenai kejayaan dari suatu kebudayaan pada masanya. Peristiwa sejarah yang pernah terjadi pasti akan berakhir dan memberikan jejak peninggalan. Indonesia sendiri memiliki berbagai jenis peninggalan seperti peninggalan bangunan bersejarah yang beragam. Khususnya di Minahasa Selatan terdapat jejak peninggalan berupa bangunan yaitu Veldbox Tumpaan dan Benteng Portugis Amurang. Dengan perkembangan teknologi saat ini, telah bermunculan berbagai jenis teknologi yang dapat dimanfaatkan sebagai sarana edukasi, contohnya Game. Penelitian memiliki tujuan untuk menghasilkan game yang dapat mengenalkan bangunan bersejarah di Minahasa Selatan dengan menggunakan metode MDLC (Multimedia Development Life Cycle) dalam pengembangannya, game ini dikembangkan dalam bentuk 3 dimensi dan bergenre adventure. Dari hasil penelitian dan kuesioner yang telah dijalankan, disimpulkan adanya peningkatan pengetahuan terhadap pengguna, juga game ini dapat menjadi salah satu media alternatif dalam mengenalkan bangunan bersejarah di Minahasa Selatan. Kata kunci — Game; Minahasa; Bangunan; Sejarah